Quantitative Analysis of Poetic Texts. - Popescu, Ioan-Ioviț (Quantitative Linguistics QL., 2015)
The book presents methods for the objective analysis of poetic language. Common objects of literary studies such as rhythm, semantic explications, interpretation and personal impressions are avoided. Only those properties of poetic texts are taken into account that could be quantified. For all methods both statistical tests, theoretical derivations, and examples are presented.